Analisis Faktor Tata Kelola dan Layanan Publik terhadap Efektivitas Retribusi Parkir Kota Blitar - Unga Prey Astanto; Dhanan Abimanto; Wasi Sumarsono (Indonesian Maritime Researchers and Lecturers, 2025)
This study analyzes the influence of Service Quality, Facilities, Supervision, and Effectiveness on Parking Levies (Retribusi Parkir) in Blitar City. Motivated by the Blitar City Transportation Agency's failure to meet its 2022 Local Own-Source Revenue (PAD) target from parking levies, this quantitative study employs Multiple Linear Regression (MLR) on a sample of 100 parking service users. Classical assumption tests confirm the regression model is normally distributed and free from multicollinearity and heteroscedasticity issues. Partially, all independent variables Service Quality (β=0.38), Facilities (β=0.200), Supervision (β=0.331), and Effectiveness (β=0.329) were found to have a positive and significant effect on Parking Levies. The Adjusted R Square value of 86.8% indicates a high predictive power of the model. Crucially, the findings highlight that Supervision and Effectiveness factors, reflecting internal governance and regulatory enforcement, are the primary determinants of successful parking levy collection, surpassing the influence of direct Facilities and Service Quality. The implications suggest a need for governance reform focusing on strict supervision and digitalization to mitigate revenue leakage.